Photovoltaic characteristics of thin films of Cu2SnS3 (1987)
We report for the first time the optical absorbtion and photovoltaic characteristics of thin films of Cu2SnS3.Films obtained by the direct evaporation of the synthesized compound were observed to be deficient in copper, while those grown in an atmosphere of copper vapour were observed to be more stoichiometric. Both sets of films are characterised by indirect and direct absorption edge propoerties. The indirect absorption edges are at 1.065 and 1.510 eV, while the direct band edges are at 1.658 and 1.770 eV for the copper deficient and stoichiometric films respectively. The stoichiometric film is characteried by p-type semiconducting properties while a Schottky type solar cell developed from it is observed to have potential photovoltaic characteristics